Knowledge, attitude, and preparedness toward IPV care provision among nurses and midwives in Tanzania - Joel Seme Ambikile; Sebalda Leshabari; Mayumi Ohnishi (BMC, 2020)
Abstract Background With increasing recognition of intimate partner violence (IPV) as a public health challenge, nurses and midwives are recognized for their crucial role in providing front-line healthcare services for IPV. This study aimed to evaluate knowledge, attitude, and preparedness related to IPV care provision in health facilities among nurses and midwives in Tanzania. Methods A self-administered anonymous questionnaire survey was conducted among nurses and midwives working in health facilities in the Mbeya region between December 2018 and January 2019. The questionnaire consisted of questions on their perceived and actual knowledge, attitudes, and preparedness to provide care in relation to IPV. Results A total of 662 (50.1%) of 1321 nurses and midwives who worked in hospitals and/or health centers in the Mbeya region participated in this study, and 461 (69.6%) completed questionnaires were included in the analysis. The proportion of nurses and midwives with high scores in IPV perceived knowledge, actual knowledge, attitude, and preparedness to provide care was 59.9%, 53.1%, 54.2%, and 54.0%, respectively. Regardless of the type of facility, gender, educational level, and work experience, the use of IPV guidelines was significantly associated with high scores in IPV perceived knowledge (P < 0.001), actual knowledge (P = 0.004), and preparedness to provide care (P < 0.001), but not attitude, which was negatively associated (P = 0.048). Regardless of the type of facility, gender, educational level, and work experience, receiving preservice IPV training was associated with high scores in IPV perceived knowledge (P < 0.001), actual knowledge (P = 0.049), and preparedness to provide care (P = 0.002), but not attitude (P = 0.192). Regardless of the type of facility, gender, educational level, and work experience, in-service IPV training was associated with high scores in IPV perceived knowledge (P < 0.001), actual knowledge (P = 0.043), and preparedness to provide care (P = 0.001), but not attitude (P = 0.063). Conclusions Although guidelines and training could improve nurses' and midwives' knowledge and preparedness to provide care regarding IPV, attitudes against IPV care are a challenge. To improve attitudes regarding IPV among front-line nurses and midwives, it is necessary to address concepts of IPV care and sympathy with potential and actual victims of IPV in pre- and in-service training in addition to providing recall-level knowledge.